Bioaccumulation and elimination of mercury in juvenile seabass (Dicentrarchus labrax) in a warmer environment - Maulvault, Ana Luísa (2020)
Warming is an expected impact of climate change that will affect coastal areas in the future. These areas are also subjected to strong anthropogenic pressures leading to chemical contamination. Yet, the consequences of both factors for marine ecosystems, biota and consumers are still unknown. The present work aims to investigate, for the first time, the effect of temperature increase on bioaccumulation and elimination of mercury [(total mercury (THg) and methylmercury (MeHg)] in three tissues (muscle, liver, and brain) of a commercially important seafood species - European seabass (Dicentrarchus labrax). Fish were exposed to the ambient temperature currently used in seabass rearing (18°C) and to the expected ocean warming (+4°C, i.e. 22°C), as well as dietary MeHg during 28 days, followed by a depuration period of 28 days fed with a control diet. In both temperature exposures, higher MeHg contents were observed in the brain, followed by the muscle and liver. Liver registered the highest elimination percentages (EF; up to 64% in the liver, 20% in the brain, and 3% in the muscle). Overall, the results clearly indicate that a warming environment promotes MeHg bioaccumulation in all tissues (e.g. highest levels in brain: 8.1mg kg-1 ww at 22°C against 6.2mg kg-1 ww at 18°C after 28 days of MeHg exposure) and hampers MeHg elimination (e.g. liver EF decreases after 28 days of depuration: from 64.2% at 18°C to 50.3% at 22°C). These findings suggest that seafood safety may be compromised in a warming context, particularly for seafood species with contaminant concentrations close to the current regulatory levels. Hence, results point out the need to strengthen research in this area and to revise and/or adapt the current recommendations regarding human exposure to chemical contaminants through seafood consumption, in order to integrate the expected effects of climate change.